Molecular dynamics and Monte Carlo simulations of the sputtering of a nanoporous solid - Rodriguez Nieva, J. F.; Bringa, Eduardo Marcial (Elsevier, 2013)
Fil: Rodriguez Nieva, J. F.. Comisión Nacional de Energía Atómica. Gerencia del Area de Energía Nuclear. Instituto Balseiro; Argentina